l e t : A = ∏ n = 2 ∞ ( 1 − n 3 1 ) & B = ∏ n = 1 ∞ ( 1 + n ( n + 1 ) 1 ) I f B A = n m w h e r e m , n a r e r e l a t i v e l y p r i m e p o s i t i v e i n t e g e r s , d e t e r m i n e 1 0 0 m + n . I t i s a N I M O P r o b l e m
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Can someone explain how you got the ratio A/B 1/2 to 3/2 ?? Simplifying gives product- (1 - 1/n^2)
Log in to reply
Write out the product (not in pi form) with each term as n 2 ( n − 1 ) ( n + 1 ) . You will see that eventually, the terms cancel each other out and the only remaining term is n n − 1 . Substituting in n = 2 gives 2 1 as required.
Alternatively, we can try to figure out a partial product. It turns out that multiply from n = 2 to m gives 2 m m + 1 . Using L'Hopital as m → ∞ easily gives 2 1 .
First, we write out the given fraction.
B A = ∏ b = 1 ∞ 1 + b ( b + 1 ) 1 ∏ a = 2 ∞ 1 − a 3 1
Since these are products, we can combine the numerator and denominator to give a single product from n = 2 to ∞ by factoring out the first term of B .
B A = 3 2 ∏ n = 2 ∞ 1 + n ( n + 1 ) 1 1 − n 3 1
We do further simplifying.
B A = 3 2 ∏ n = 2 ∞ n 3 ( n ( n + 1 ) + 1 ) ( n 3 − 1 ) ( n ( n + 1 ) )
= 3 2 ∏ n = 2 ∞ n 3 ( n 2 + n + 1 ) n ( n − 1 ) ( n 2 + n + 1 ) ( n + 1 )
= 3 2 ∏ n = 2 ∞ n 1 ( n − 1 ) ( n + 1 )
From this, we note that terms cancel out until we are left with n n − 1 = 2 1 .
Finally,
B A = 3 2 ( 2 1 ) = 3 1 .
m = 1 , n = 3 → 1 0 0 m + n = 1 0 3
Problem Loading...
Note Loading...
Set Loading...
A = ∏ n = 2 ∞ ( 1 − n 3 1 ) = ∏ n = 2 ∞ ( n 3 ( n − 1 ) ( n 2 + n + 1 ) ) B = ∏ n = 2 ∞ ( 1 + n ( n + 1 ) 1 ) = ∏ n = 2 ∞ ( n ( n + 1 ) ( n 2 + n + 1 ) ) B A = 2 3 2 1 [ t h e o t h e r t e r m s w o u l d c a n c e l ] B A = 3 1 ⟹ m = 1 ; n = 3 ∴ 1 0 0 m + n = 1 0 3